THE EFFECT OF PRICE, PROMOTION AND SERVICE QUALITY ON PURCHASING DECISIONS AT ALFAMART JAMBI - JUNAIDI; Mukti Harianto (Widya Dharma Journal of Business - WIJoB, 2026)
This research is based on the rapid growth of many Indonesian retail industries in recent years. The aim of this study is to determine the influence of price, promotion, and service quality on consumer purchasing decisions at Alfamart Jambi. The study used a quantitative method with a survey approach involving 150 respondents. Data collection was conducted through the distribution of questionnaires to Alfamart Jambi consumers as research respondents. The data analysis technique used was multiple linear regression analysis with classical assumption tests. The results of the study indicate that partially, the price and promotion variables have a positive and significant effect on purchasing decisions, while service quality has no significant effect. However, simultaneously, the three independent variables of price, promotion, and service quality have a significant effect on purchasing decisions at Alfarmart Jambi. The coefficient of determination (R²) value of 0.792 indicates that 79.2% of the variation in purchasing decisions can be explained by this research model, while the remaining 20.8% is influenced by other factors outside this study. The research results show that competitive prices, attractive promotions, and good service quality can increase consumer purchasing decisions at Alfamart Jambi.